Corporate Governance, Social Responsibility, Innovation, and Sustainable Business Development Goals - Helfaya, Akrum; Aboud, Ahmed (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the key concepts and contemporary issues related to corporate governance, social responsibility, innovation, and sustainable business development goals. It highlights the importance of integrating these principles into the operations of modern businesses. The reprint aims to explore these concepts, providing theoretical foundations, practical frameworks, and real-world examples to inspire responsible, innovative, and sustainable business practices.